Meningkatkan Hasil Belajar PKn Siswa Kelas V dengan Model Kooperatif Tipe Student Team Achievement Divisions - Antonius Tri Wiratno (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
The successfulness of learning process at school is influenced by several factors. Result of initial observation shows that the learning process of Civics subject at SDN 16 Batang Anai Kabupaten Padang Pariaman was still dominated by teacher. Hence, only 50% of students reaching the learning achievement standard of 75. This research was aimed to improve students’ learning achievement of Civics subject by using cooperative learning model of STAD. Subject of this research are the fifth grade students at SDN 16 Batang Anai Kabupaten Padang Pariaman. This class action research was held in two cycles with three meetings for each cycle. Data of research were obtained through observation and students’ test result. Data were analyzed quantitatively and qualitatively. Researcher set the learning achievement standard as 75. After cycle I, students’ learning achievement is only 64. After cycle II, students’ learning achievement is improved and exceeds the standard, i.e. 81. These show that implementation of cooperative learning model of STAD can improve students’ learning achievement of Civics subject.